Analisis Jual Beli Laptop Online Seluruh Tangerang Di Facebook - Cinto Pastita; Aist Istiqomah; Muhammad; Syaikal Fathan Muzakki; Pia Khairontun Nisa (Jurnal Ekonomi dan Bisnis Digital, 2024)
Social media has rapidly evolved in the digital era, becoming a vital tool in the formation of virtual communities that connect individuals with shared interests or goals, transcending geographical boundaries. These communities provide platforms for sharing knowledge, emotional support, and information, fostering social connections and enhancing cross-cultural inclusion. A concrete example is the online laptop buy-and-sell community on Facebook, which functions not only as a marketplace but also as a social space that facilitates both practical and emotional interactions among members.This research aims to examine the social and economic impacts of such virtual communities, focusing on how interactions within the community influence consumer behavior, shopping patterns, and members' social relationships. Additionally, the study explores the motivations behind using social media as a buy and sell platform and the role of social support and networks in shaping members’ social identity and solidarity. It is expected that this research will provide insights into the dual function of virtual communities as transactional platforms and social spaces that significantly impact the lives of their members.